2020
DOI: 10.1126/science.aba9301
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophilic inflammation in the respiratory mucosa predisposes to RSV infection

Abstract: The variable outcome of viral exposure is only partially explained by known factors. We administered respiratory syncytial virus (RSV) to 58 volunteers, of whom 57% became infected. Mucosal neutrophil activation before exposure was highly predictive of symptomatic RSV disease. This was associated with a rapid, presymptomatic decline in mucosal interleukin-17A (IL-17A) and other mediators. Conversely, those who resisted infection showed presymptomatic activation of IL-17– and tumor necrosis factor–related pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
98
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(114 citation statements)
references
References 68 publications
2
98
1
Order By: Relevance
“…As previously reported, prior to viral inoculation (baseline) [8], there were no significant difference in bacterial alpha diversity (Richness, P = 0.948; Shannon-Weiner, P = 0.263; Simpsons, P = 0.166) or beta diversity (Bray-Curtis dissimilarity, R 2 = 0.055, P = 0.087).…”
Section: Microbial Changes Over Timesupporting
confidence: 78%
See 2 more Smart Citations
“…As previously reported, prior to viral inoculation (baseline) [8], there were no significant difference in bacterial alpha diversity (Richness, P = 0.948; Shannon-Weiner, P = 0.263; Simpsons, P = 0.166) or beta diversity (Bray-Curtis dissimilarity, R 2 = 0.055, P = 0.087).…”
Section: Microbial Changes Over Timesupporting
confidence: 78%
“…Thirty-seven healthy non-smoking individuals aged between 18 and 50 years old were recruited into the study (Table 1) [14]. Participants were screened for immunodeficiencies, respiratory diseases and medications [8].…”
Section: Study Design and Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies on the interaction between climate changes and respiratory barrier dysfunction indicated not only higher incidence of viral infection but also higher vulnerability of nasal mucosa through increased incidence of nosebleed in the emergency departments in the conditions of low temperature and low humidity (43). A recently published study that exposed volunteers to respiratory syncytial virus (RSV), one of the pathogens responsible for the common cold, demonstrated that pre-existing inflammation in the respiratory mucosa was a risk factor for infection (44), which further supports the importance of mucociliary dysfunction and respiratory barrier impairment for infection with respiratory viruses.…”
Section: Figure 2 |mentioning
confidence: 99%
“…However, there is a paucity of information on immune responses against SARS-CoV-2 infection in the upper airway (17). Minimally invasive sampling techniques of the nasal mucosa are well-tolerated, and highly useful in human challenge models of respiratory syncytial virus and Streptococcus pneumoniae (18, 19). Given importance of the nose in SARS-CoV-2 infection (20), understanding the host–viral interaction at the nasal mucosa could provide additional insights to understand and potentially modulate COVID-19 prognosis.…”
Section: Introductionmentioning
confidence: 99%